Effect of LI4 and LI11 electro- acupressure on pain intensity and disability in pregnant women with low‐back and pelvic pain: A randomized controlled trial - Parvaneh Alirezaei; Hamideh Pakniat; Ahad Alizadeh; Fatemeh Ranjkesh (Mashhad University of Medical Sciences, 2021)
Introduction: Back and pelvic pain is one of the most common problems during pregnancy. Acupressure is one of the treatment strategies. Therefore, this study was performed with aim to determine the effect of electro-acupressure of LI4 and LI11 on the severity and disability of in pregnant women with low back and pelvic pain. Methods: This randomized clinical trial study was performed on 101 pregnant women with low back and pelvic pain referred to Booeinzahra health centers from April to November 2020. The subjects were divided into intervention and control groups using block random allocation. The intervention group participated in 12 sessions of electro-acupressure on Heogu and Quchi from 26 to 32 weeks of pregnancy. The control group received standard prenatal care. The Roland Morris Disability Questionnaire and Visual Analogue of Pain were completed in both groups before, 2 and 4 weeks after the intervention. Data were analyzed using R software and mixed effects model tests and post hoc test. P< 0.05 was considered statistically significant. Results: The results of the study showed that 4 weeks intervention significantly reduced pain intensity (6.42 ± 0.83, 3.00 ±1.04) and disability (14.62 ± 1.29, 7.9±2.22) in the intervention group compared to the control group (P <0.001). Conclusion: Electrical stimulation of Hugo and Kochi needles during pregnancy can improve the severity of pelvic and low back pain and disability; it is recommended as a non-pharmacological method for low-risk pregnant women.